Increasing Taxes on Tobacco in Low and Middle-Income Countries : Hurting or Saving the Poor? - Fuchs Tarlovsky, Alan; Gonzalez Icaza, María Fernanda (World Bank, Washington, DC, 2020)
Policy makers hesitate to increase tobacco taxes over concerns about taxes being regressive and potentially increasing poverty and inequality. This note summarizes a set of studies of the effects of raising tobacco taxes in 11 low and middle-income countries using an extended cost-benefit analysis (ECBA) and harmonized national household budget survey data and introduces the TOBACTAX Tool. The studies find that demand price elasticities for tobacco products are larger among lower-income households and that the poor receive the largest long-term gains from tobacco taxation. Tobacco taxes have progressive long-term effects due to lower medical expenses and added years of productive life, which contribute to poverty reduction in most countries studied. TOBACTAX Tool can help replicate such analyses elsewhere.